INTERNAL AUDIT OF FINANCIAL ASSETS IN BUDGETARY ORGANIZATIONS CASE AND TAXALITY (Spectrum Journal of Innovation, Reforms and Development, 2022)
Internal audit in budget organizations is an activity aimed at verifying compliance with legislation and monitoring the preparation and execution of estimates by the organization, ensuring the reliability of financial reporting data, compliance with budget-estimate discipline, purposeful and rational spending of funds. Organization of the internal audit related to the adoption of the budget code and the introduction of the efficiency principle is one of the most urgent issues of the day. A budget organization is a non-profit organization established in accordance with the decision of the state authorities in order to perform state functions, maintained at the expense of the state budget.